2017
DOI: 10.1007/s12185-017-2383-1
|View full text |Cite
|
Sign up to set email alerts
|

A low birth weight infant with no malformations delivered by a primary immune thrombocytopenia patient treated with eltrombopag

Abstract: Primary immune thrombocytopenia (ITP) is defined by a low platelet count secondary to antibody-mediated platelet destruction or reductions in platelet production. Although eltrombopag is a thrombopoietin receptor agonist that increases platelet production in refractory or relapsed ITP, the influence on pregnancy is limited. We present the case of a pregnant 25-year-old ITP patient referred to our hospital with a history of two induced abortions. After eradication of Helicobacter pylori and with oral prednisolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…All available published data are from 11 available case reports, and all show a platelet response. [119][120][121]141,[231][232][233][234][235][236][237] Romiplostim and eltrombopag may cross the placenta and could cause potential harm to the fetus. 119,120,227 In the 11 cases reviewed here, there were no safety concerns.…”
Section: Management Of Pregnant Patients With Itp Failing Initial Trementioning
confidence: 99%
See 1 more Smart Citation
“…All available published data are from 11 available case reports, and all show a platelet response. [119][120][121]141,[231][232][233][234][235][236][237] Romiplostim and eltrombopag may cross the placenta and could cause potential harm to the fetus. 119,120,227 In the 11 cases reviewed here, there were no safety concerns.…”
Section: Management Of Pregnant Patients With Itp Failing Initial Trementioning
confidence: 99%
“…119,120,227 In the 11 cases reviewed here, there were no safety concerns. [119][120][121]141,[231][232][233][234][235][236][237] TPO-RAs are not recommended except in very serious cases; if used, romiplostim may be preferred given its fewer off-target effects (lack of hepatic toxicity and iron chelation) and limited safety database.…”
Section: Management Of Pregnant Patients With Itp Failing Initial Trementioning
confidence: 99%
“…medicated eltrombopag from 36th gestational week to a case complicated with autosomal dominant thrombocytopenia, i.e., MYH9 -related disease, and successful platelet increase was observed [ 15 ]. Four cases of ITP, including the present case, were treated with eltrombopag (cases 3-6) [ 16 - 18 ]. Case 3 showed slight platelet increase necessitated with platelet transfusion for vaginal delivery and case 4 achieved platelet increase over 60 × 10 9 /L, however, platelet count fell to 19 × 10 9 /L at 36th week of gestation, where preeclampsia could not be ruled out from the cause of underlying pathology [ 16 ], and the patient subsequently needed platelet transfusion for delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in fetal weight at birth was seen only at an extremely high doses of 100 µg/kg, and doses of 1–10 µg/kg used in cases of ITP are considered to have little effect on fetal weight at birth. On the other hand, Suzuki et al reported an infant born with a low birth weight in a case of human pregnancy treated with eltrombopag [ 15 ]. However, we did not investigate the effect of eltrombopag in this study due to its limited specificity and activity on humans and chimpanzees [ 16 ].…”
Section: Discussionmentioning
confidence: 99%